Auditoría de Gestión en la Cooperativa de ahorro y crédito Tulcán Ltda. - Flores Vinueza, Evelyn Victoria (2014)
This research was designed to analyze the efficiency, effectiveness, and economy of the resources used by the Savings and Credit Cooperative "Tulcán" Ltda., including human, material, financial, and technological resources, through the application of a Management Audit, which constitutes a highly effective tool for evaluating the results obtained.During the study and analysis, various research methods were applied to assist in the collection of information through observation, surveys, interviews, and the respective methodological guide from the Universidad Regional Autónoma de los Andes, which helped to understand the different activities to be investigated. Furthermore, understanding how to conduct a management audit has allowed us to understand the facets of each of the operational areas of the “Tulcán” Savings and Credit Cooperative Ltda., as well as the activities of each employee. Once the audit was conducted, it became clear that the shortcomings that hinder organizational development were due to a failure to adhere to current strategic planning, the lack of an updated job manual, the lack of advertising and promotion, and the lack of trained personnel in the business areas. These have been the factors hindering the efficient development of the "Tulcán" Savings and Credit Cooperative Ltda. Currently, the application of this audit in all types of companies will allow researchers to analyze the performance of administrative management in order to generate the necessary corrective measures for timely decision-making.